Inductive versus deductive approaches to teaching grammar at secondary schools in the East Coast of Malaysia: Teachers' perspectives / Nur Hidayah Md Yazid - Md Yazid, Nur Hidayah (2014)
If language teachers are not able to distinguish the roles of inductive and deductive approaches in teaching grammar, students would not be learning what is targeted to be acquired, which definitely would affect the balance of the acquisition or learning process of the second language as a whole. There are quite a scarce number of studies conducted from the viewpoint o f ESL teachers particularly in the east coast of Malaysia, which are Kelantan, Terengganu and Pahang Hence, the purpose of this study is to capture the insights of the ESL teacher’s current grammar teaching approach in these areas in ensuring their students’ effective learning. This study uses a generic qualitative approach and a set of interview questions were solicited in person to 10 ESL teachers who are selected using purposive sampling technique from among those currently teaching at secondary schools in the east coast of Malaysia. The first research question of this study reveals that the highest frequency of preferred approach is the deductive approach that is believed to be better for the low proficient students. Then, the second research question discloses the factors that are the mostly influence the respondents’ choice of approach, which are school area, followed by availability of good materials, gender of the students, the teachers’ qualification, the students’ proficiency level in English, and teaching time or periods. Next, the third research question reveals that the problems occur while using the inductive approach is lack of students’ participation, negative attitudes among students and superiors, and students’ lack of confidence. On the other hand, the problems that occur while using the deductive approach are difficulty in coping with its rigidity, over generalization of rules, and lack of autonomous learning. Finally, the fourth research question uncovers that the most frequently suggested solutions by the respondents are to have an abundance of good materials, alternate teaching approaches, keep reminding students of the importance of grammar, and conduct more English programs. The implications of this study is to include more respondents that come from various backgrounds of education, other areas of Malaysia, other programs besides TESL yet are required to teach English, and years of teaching experience. It is also recommended to have a much bigger sample size and different research designs in order to make the results more convincing. Additionally, future research may involve the students as the sample as well in order to obtain the perceptions from the students regarding grammar teaching and learning.